Role of angiopoietin-like 4 protein on neutrophil heterogeneity during wound healing - Wong, David Meng Kit (Nanyang Technological University, 2023)
Proper wound healing is critical in repairing damaged tissue and preventing infections, failing which, complications such as scarring and systemic infections may arise. Neutrophils are one of the first immune cells recruited to the wound site and are responsible for wound healing. However, their timely clearance is essential for proper wound closure. Recent studies have indicated that neutrophil heterogeneity exists in various pathological states. Using single-cell RNA sequencing (scRNA-seq) and clustering algorithms, we report seven neutrophil subpopulations (G3/4, G5a, G5b, G5c, G6a, G6b, and GM) in the wound microenvironment. Our scRNA-seq data demonstrated that the knockout of angiopoietin-like 4 (Angptl4), a matricellular protein implicated in many inflammatory diseases, resulted in increased G5a and G6a neutrophils in Angptl4-/- mice compared to Angptl4+/+ mice. A pseudotime analysis revealed that G6a neutrophils mature from G5a neutrophils, forming a terminal lineage exhibiting proinflammatory properties. We successfully isolated G5a neutrophils using anti-CD93 antibodies and validated its identity based on its expression profile. Using a casein-induced intraperitoneal neutrophilia model, we confirmed that G5a-to-G6a neutrophil maturation was impaired in Angptl4-deficient mice, causing prolonged inflammation. In conclusion, we have optimized the methodology to isolate G5a neutrophils and revealed a crucial role of Angptl4 in neutrophil heterogeneity.